Cost analysis of the education of students in School of Public Health Kerman University of Medical Sciences Iran using activitybased costing model - Ali-Akbar Haghdoost; Marjan Amirimoghadam; Mahshid Loloei; Mohammad-Reza Baneshi; Faezeh Sabbah; Mohammad-Hossein Mehrolhassani (Kerman University of Medical Sciences, 2014)
Background & Objective: Quantifying real costs in total and per student is one of the key objectives of budgeting in longterm plans for higher education sector without any doubt this will improve the performance of universities However the evidences and experiences in this regard are very limited within Iran The purpose of this study was to estimate and analyze all costs of a school (as a model) compatible with activitybased costing in the logics of operating budgeting   Methods: Having reviewed all available relevant documents of School of Public Health Kerman University of Medical Sciences in one academic year (201011) real costs were extracted and categorized In the same time all available facilities (classes laboratories library computer rooms and common rooms) human resources students and infrastructures of the school were surveyed The cost data were grouped into five sections: training costs research costs administrative costs current supportive costs and maintenance/development costs   Results: The total cost of School of Public Health was 24726 million Iranian Rial (IRR) consisted of 18850 IRR for teaching costs 1894 IRR for research costs 2519 IRR for administrative costs and 1463 IRR for maintenance and current costs The total per student cost was 3111 IRR The total per postgraduate student cost was 25 times more than of undergraduate students   Conclusion: A main part of the costs particularly salaries is out of hand of direct managers of the school These costs are usually hidden and are not presented in costs at the school level It seems that fixed salary of academic staff inflated human costs while it is suggested that with a better educational management the system could increase their responsibilities and improve their productivities Our computation as a model may help medical universities around the country to create a clear picture of their costs in line with the rules of operating budgeting